A RECURRENCE METHOD FOR SIMPLE CONTINUOUS LINEAR PROGRAMMING PROBLEMS - Wen, Ching-Feng; Wu, Yan-Kuen; Lur, Yung-Yih (Journal of the Chinese Institute of Industrial Engineers, 2009)
In this paper, we discuss a special class of continuous linear programming problems which can be called simple continuous linear programming problems (SP). A practical and efficient method for finding an approximate optimal value and optimal solution of (SP) is presented. The main work of computing an approximate optimal value in the provided method is only to solve finite linear programming problems by using recurrence relations. Furthermore, a simple algorithm can be employed not only to easily solve the (SP) problem but also to provide an error bound of optimal value as well. Some numerical examples are given to implement the algorithm.